Structural and millimeter-wave characterization of flux grown Al substituted barium hexaferrite single crystals. Issue 10 (December 2015) - Vinnik, D.A.; Ustinov, A.B.; Zherebtsov, D.A.; Vitko, V.V.; Gudkova, S.A.; Zakharchuk, I.; Lähderanta, E.; Niewa, R.
Abstract: Single crystals of barium hexaferrites with compositions BaFe12 O19 and BaFe11.5 Al0.5 O19 were grown from carbonate flux. The Al substitution results in a reduction of the unit cell volume from 697.54(7) Å 3 for unsubstituted hexaferrite to 695.93(3) Å 3 for the Al-substituted phase and the Curie temperature from 450 to 420 °C. The magnetization of BaFe11.5 Al0.5 O19 samples was measured between 3 and 300 K in external magnetic fields of 0.001 and 0.05 T. The temperature dependence of the magnetization at a magnetic field of 0.001 T demonstrates irreversibility, which disappeared at 0.05 T field. Millimeter-wave characterization of BaFe11.5 Al0.5 O19 slabs loaded in a WR-10 waveguide was carried out in the frequency range of 75 to 100 GHz. In this range electromagnetic resonances were observed at the frequencies of 78.6 GHz and 96.3 GHz. The resonant microwave absorption level was controlled by value of bias magnetic field.